The Urgency Of Registering Marriage Agreements For Husband And Wife (Study At The Population And Civil Registry Office Of Medan City) - Mhd. Ridho Eko Prasojo (Ilmu Hukum Prima (IHP), 2025)
Registration of Marriage Agreement is a series of marriage implementation. Therefore, marriage registration is an inseparable part of the implementation of the marriage in question (husband and wife). Marriage agreements experienced a shift when there was Constitutional Court Decision No. 69 / PUU-XIII / 2015, namely: "At the time, before or during the marriage bond, both parties with mutual consent can enter into a written agreement that is legalized by a marriage registrar or notary, after which the contents also apply to third parties as long as the third party is involved." The shift in norms on marriage agreements is seen from "when" the marriage agreement was made. This study aims to analyze how the registration of husband and wife marriage agreements (study at the Medan City Population and Civil Registration Office) after Constitutional Court Decision No. 69/PUU-XVIII/2015 using empirical juridical methods with a qualitative approach, this research involves document analysis, interviews with Medan City Population and Civil Registration Office employees. The research findings reveal that the Validity of Marriage Agreement Registration According to Indonesian Positive Law is regulated in Article 29 paragraph (1) of Law No. 1 of 1974 Jo. Constitutional Court Decision No. 69/PUU-XIII/2015. For Muslim couples register marriage agreements at the Office of Religious Affairs (KUA) and for couples of non-Muslim religions register their marriage agreements at the Office of Population and Civil Registration (Disdukcapil) and the Urgency of Marriage Agreement Registration at the Office of Population and Civil Registration of Medan City is firstly to fulfill the requirements in accordance with Article 29 paragraph (1) of Law No. 1 of 1974 Jo. Constitutional Court Decision No. 69/PUU-XIII/2015, secondly, the registration of a marriage agreement can be useful, among other things, to find out the legal certainty regarding the date of creation and the validity of the marriage agreement.